Antioxidant and Antiaging Properties of Ethanolic Ripe Sesoot Fruit Extract (Majalah Kedokteran Bandung, 2024)
Skin aging can be characterized by changes in skin, such as the appearance of wrinkles and loss of skin moisture. Some elements that might lead to cell damages and aging are free radicals through the increase of the activities of hyaluronidase and tyrosinase. Bioactive compounds found in sesoot (Garcinia picrorhiza Miq.) are known for their antioxidant properties, which may reduce excessive amounts of free radicals in the body and act as an antiaging agent by inhibiting hyaluronidase and tyrosinase activities. This study aimed to examine the antioxidant, anti-hyaluronidase, and anti-tyrosinase properties found in Ethanolic Extract Ripe Sesoot (EERS). The ethanol extract of ripe sesoot fruit obtained from LIPI, Bogor Botanical Garden was used for the antioxidant and antiaging assays conducted at PT Aretha Medika Utama in December 2016. The activity of antioxidants was measured as the Ferric Reducing Antioxidant Power (FRAP) of the EERS, while the antiaging assays were performed through the inhibition activity of hyaluronidase and tyrosinase. Results indicated that the EERS has a higher FRAP activity (17.58 Î¼M Fe (II)/Î¼g) than xanthone (2.54 Î¼M Fe (II)/Î¼g) at the highest concentration of sample of 5,000 µg/mL. The anti-hyaluronidase of the EERS exhibited lower activity (IC50 of 619.21±12.15 µg/mL) than xanthone (IC50 of 365.55±25.10 µg/mL) and the tyrosinase inhibitory assay demonstrated a lower activity of EERS (IC50 of 1060.68±12.81 µg/mL) compared to xanthone (IC50 of 218.33±9.73 µg/mL). To conclude, EERS shows antioxidant and antiaging properties.
Keywords: Antioxidant; Garcinia picrorhiza; hyaluronidase; skin aging; tyrosinase